2019
DOI: 10.1097/md.0000000000015849
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status moderates the association between patient satisfaction with community health service and self-management behaviors in patients with type 2 diabetes

Abstract: The objective of this study was to examine the association between patient satisfaction with community health service (CHS) and self-management behaviors in patients with type 2 diabetes mellitus (T2DM). In all, 1691 patients with T2DM from 8 community health centers in 5 provinces in China participated in the present study. The dependent variables included 4 measures of self-management behaviors: regular self-monitoring of blood glucose (SMBG), prescribed medication adherence, recommended dietary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“…Some studies found higher satisfaction among the population with lower education level. 15 Some studies reported the opposite results, 37 while others had discovered no significant relationship. 38 In this study, people with lower education levels were found to be more satisfied with health services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found higher satisfaction among the population with lower education level. 15 Some studies reported the opposite results, 37 while others had discovered no significant relationship. 38 In this study, people with lower education levels were found to be more satisfied with health services.…”
Section: Discussionmentioning
confidence: 99%
“…It may be because people with lower educational levels had better medication adherence. 15 Conversely, people with higher education were more inclined to ask questions about what was being told, and their medication adherence was not good. Meanwhile, people with higher education levels are expected to be given preferential treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review has summarized the domains used for patient satisfaction measurement in Saudi Arabia, which includes communication attributes, relational conduct, technical skill, personal qualities, availability, and accessibility [12]. Meanwhile, many empirical studies have been conducted to measure patient satisfaction in different countries, such as England [13], Pakistan [14,15], China [16,17,18,19,20], Germany [21], Saudi Arabia [22], the U.S. [23], Canada [24], Italy [25], and South Africa [26]. Among these studies, multifarious measures were employed and numerous determinants of patient satisfaction were identified.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of community health service, it proposed that patients' satisfaction with community health service was moderate, high satisfaction with the community health service shown better medication adherence and regular self-monitoring of blood glucose, and these associations varied by socioeconomic status [9]. In particular, team-based care can improve patients' glucose levels, blood pressure, and lipid levels based on community preventive services task force [10].…”
Section: Introductionmentioning
confidence: 99%